Meningkatkan Konsentrasi Belajar Menggunakan Metode Teams Games Tournament Pada Mata Pelajaran PAI - Al-Husen, Putri Lailiyatul Azizah; Hafizhah, Salwa Hafizhah; Rizqiyah, Sifa Ikhsaniandita Rizqiyah; Makbul, M. Makbul; Farida, Nur Aini Farida (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This research seeks to increase the learning concentration of class V students at SDN Cikampek Barat IV. The research methodology used in this research is called classroom action research. Concentration is necessary in learning because it facilitates students' understanding and retention of the information presented by the teacher. Two cycles, each consisting of four stages—1) Planning, 2) Action, 3) Observation, and 4) Evaluation reflection—constitute this research. For fifth grade students at SDN Cikampek Barat IV, the Teams Game Tournament method can increase students' learning concentration in PAI learning in line with the activities that have been carried out starting from the pre-cycle, cycle I action, and cycle action. The percentage of completion in the pre-cycle was originally only 44 .4% in cycle I increased to 76.9% and in cycle II increased to 96.7%. From the results of the completeness presentation, we can see that the TGT type cooperative learning model can increase student concentration in learning.